Pierson Syndrome: An Update - Conegundes, Ana Flávia; de Lima Silva, Nayara; Silva, Felipe Rodrigues Lima Resende; de Paiva Santos, Maria Luíza Dias; Vieira da Silva, Henrique Faustino; dos Santos, Wesley Cardoso; Simões e Silva, Ana Cristina; Santos Borges, Rafael Dos (Current Pediatric Reviews, 2026)
Pierson syndrome (PS) is a rare autosomal recessive disorder, primarily characterized by (1) congenital nephrotic syndrome, (2) ocular abnormalities, and (3) neurodevelopmental deficits. It is caused by mutations in the <span class=
Keywords: glomerular basement membrane